Avelumab induces greater Fc-Fc receptor-dependent natural killer cell activation and dendritic cell crosstalk compared to durvalumab - Nicole Osborne; Amit Rupani; Vladimir Makarov; Timothy A. Chan; Raghvendra M. Srivastava (OncoImmunology)
Several FDA-approved anti-PD-L1 (programmed cell death ligand-1) monoclonal antibodies (mAbs) are used to treat cancer. While these mAbs primarily target and intercept PD-L1:PD-1 inhibitory signaling in T-cells, the Fc-domains of these mAbs are distinct, and the unique cellular cascades triggered by differing Fc-domains of PD-L1 mAbs have not been directly investigated. In this study, we compared the innate immune effects of two widely used anti-PD-L1 IgG1 mAbs which bear distinct Fc-domains, avelumab (native-Fc) and durvalumab (mutated-Fc), using two-cell and three-cell co-culture systems containing Natural Killer cells (NK-cells), dendritic cells (DCs) and various tumor cell lines of multiple cancer origins. We show a robust enhancement in NK-cell effector function, DC maturation, reciprocal NK:DC crosstalk and DC editing that is unique to avelumab treatment using multiple functional immune assays. By transcriptomic analysis, we show for the first time pivotal differences in gene sets involved in NK-cell effector function, DC maturation, immunoregulatory interactions, and cytokine production between innate immune cells treated with avelumab versus durvalumab. Furthermore, we report several previously unknown Fc-receptor-associated biological pathways uniquely triggered by avelumab. Our findings elucidate novel mechanisms of Fc-dependent actions of PD-L1 mAbs which may inform their use in future clinical trials.